Kinerja Dinas Perhubungan Kabupaten Tabanan dalam Pengelolaan Retribusi Parkir - Eka Rahayu, Ni Putu Santi; Yudartha, I Putu Dharmanu; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2019)
ABSTRACT Transportation Goverment Agency of Tabanan Regency is the government's institute as the practitioner in improving the quality of transportation services, especially management of parking fees at the public roadside. This research uses descriptive qualitative methods. The results of this study indicate that the target and the realization of public roadside parking fees for the last three years (2015-2017) continues to increase. But in the other side, there are still problems in terms of input indicators that need to be addressed such as the quality of human resources and the potential for parking retribution seen from the number of vehicles increasing each year which has implications for the availability of parking spaces. One strategy to improve the performance of the Tabanan Regency Transportation Service in collecting parking fees at the public roadside is the increase in parking rates and the use of electronic parking machines. Keywords: The Performance of Transportation Government Agency, Management, Parking Retribution